PERLINDUNGAN HUKUM TERHADAP PEKERJA BERSTATUS PERJANJIAN KERJA WAKTU TERTENTU (PKWT) MENURUT UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Asuan, Asuan (Solusi, 2019)
This study is a normative juridical approach with an approach to problems that see in terms of applicable laws and regulations, especially regarding labor law / labor. This study uses secondary data with the preparation of a conceptual framework, to obtain legal materials in the form of theories, concepts and legal principles obtained from the literature, among others, books, documents, articles, and other literature. Legislation, namely Law No. 13 of 2003 concerning Labor, the Civil Code and other legal regulations relating to problems. The results of the discussion, namely the protection of workers with an inter-time employment agreement (PKWT) according to Law Number 13 of 2003 concerning Employment, namely: Protection of work hours namely 7 (seven) hours in 1 (one) day and 40 hours 1 (one) week for 6 (six) working days in 1 (one) week; or 8 (eight) hours in 1 (one) day and 40 hours 1 (one) week for 5 (five) working days in 1 (one) week. (Article 77 paragraph 1); Protection against wages, namely provincial minimum wages and district / city minimum wages (Article 88 paragraph (3) letter a); protection of welfare, that is workers / laborers and their families have the right to obtain social security workers. and includes family planning services, child care, workers' housing, worship facilities, sports facilities, canteen, health, recreation and the establishment of cooperative facilities, of course the provision of these facilities is carried out with the company's ability (Article 99 paragraph 1 and 100 verses 1 and 2) , and Protection of Social Security, namely the Social Security Program includes collateral for death, work accident insurance, old age guarantee and health care guarantee (article 99). The constraints in legal protection of workers in certain time work agreements (PKWT) are related to regulations, relating to work agreements and related to supervision